Reason and responsibility : Readings in some basic problems of Philosophy - Feinberb, Joel; Shafer- Landau, Russ (Boston, Massachusetts : Wadsworth Cengage Learning, 2013)
The Conviction underlying this volume is that introducing the college student to philosophy by means of a few representative problems examined in great details is far preferable to offering a "little bit of everything," with each branch of philosophy, each major "ism," and each major historical period represented with scrupulous impartially , even though the articles may have a little relevance to one another.
Part -- 1. reason and religious beliefs -- 2. human knowledge: its ground and limits -- 3. mind and its place in nature -- 4. determinism, free will, and responsibility -- 5.morality and its critics.
Keywords: PHILOSOPHY